Interpreting the Consequences of Metformin Accumulation in an Emergency Context: Impact of the Time Frame on the Blood Metformin Levels - Jean-Daniel Lalau; Farshad Kajbaf (International Journal of Endocrinology)
Objective. To clarify the link between metformin accumulation and its metabolic consequences by taking the time frame for metformin measurement into account. Research Design and Methods. Our database was studied for cases of metformin accumulation and lactic acidosis status available on admission, and then we selected patients in whom arterial pH, blood lactate, and plasma and erythrocyte metformin levels had been determined at the same time point. Results. Seventeen reports were studied on 16 patients, of whom 10 presented lactic acidosis. The time interval between admission and comprehensive testing ranged from 0 to 52 hours. The study parameters were determined simultaneously on admission in only 4 patients. In the 9 patients with lactic acidosis on admission and a delayed metformin assay, lactic acidosis persisted in 6 cases and had resolved in 3 cases by the time the blood sampling for metformin assay was performed. Conversely, lactic acidosis developed after admission in one case. Conclusions. Caution must be taken when interpreting the consequences of metformin accumulation in an emergency context: the patient’s lactic acidosis status will have changed by the time the metformin assay is performed, even though metformin accumulation may still be present.